2019
DOI: 10.2465/jmps.181119b
|View full text |Cite
|
Sign up to set email alerts
|

Transformation process of amorphous magnesium carbonate in aqueous solution

Abstract: Amorphous magnesium carbonate (AMC) is an important phase in the early formation stage of magnesium carbonate. In this study, precipitation experiments were conducted to clarify the formation and transformation process of AMC in aqueous solution. Fine AMC particles precipitated, immediately after mixing of Na 2 CO 3 and MgCl 2 solutions. Chemical composition of the AMC was determined to be approximately MgCO 3 •2H 2 O although two hydration states were expected to exist for AMCs. Subsequently, the AMC transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The water content corresponds to the n value in the AMC chemical formula MgCO 3 •xH 2 O. From the weight loss results, it was calculated that AMC20, AMC60, and AMC80 had x values of 2.2, 1.9, and 1.6, respectively, suggesting that the average chemical formula of the AMC samples is approximately MgCO 3 •2H 2 O, which is in good agreement with that of AMC obtained at 15°C 14 . As mentioned below, since there are no substantial structural differences in AMC samples, the variation of water content does not affect the medium-range structural order of AMC.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The water content corresponds to the n value in the AMC chemical formula MgCO 3 •xH 2 O. From the weight loss results, it was calculated that AMC20, AMC60, and AMC80 had x values of 2.2, 1.9, and 1.6, respectively, suggesting that the average chemical formula of the AMC samples is approximately MgCO 3 •2H 2 O, which is in good agreement with that of AMC obtained at 15°C 14 . As mentioned below, since there are no substantial structural differences in AMC samples, the variation of water content does not affect the medium-range structural order of AMC.…”
Section: Resultssupporting
confidence: 72%
“…Amorphous magnesium carbonate (AMC), which can be produced by mixing aqueous solutions containing Mg 2+ and CO 3 2− ions 14 , is a precursor of these crystalline magnesium carbonate hydrate materials. At lower temperatures (below approximately 55 °C), AMC crystallizes into nesquehonite by vigorous stirring in an aqueous solution 15,16 , while at higher temperatures (above approximately 55 °C), hydromagnesite forms [16][17][18] .…”
mentioning
confidence: 99%
“…Previously, dypingite along with nesquehonite was successfully synthesised from AMC (e.g., Tanaka et al 2019), but it was rarely reported in assemblage with natural/synthetic MHC (e.g., Dahl and Buchardt 2006). In most works hydromagnesite (e.g., Rodriguez-Blanco et al carbonates (e.g., Nishiyama et al 2013;Fukushi et al 2017) are considered to be the main Mg-phase concomitant to MHC.…”
Section: Monohydrocalcite Formation Conditionsmentioning
confidence: 99%
“…The metastable phase of carbonate (i.e., AMC and MHC) have not been identified in surface materials in previous remote‐sensing studies (e.g., De Sanctis et al., 2016), although the presence of hydrohalite (NaCl·2H 2 O) and its dehydration product (NaCl) have been suggested to be present near the bright spots of Occator Crater of Ceres (De Sanctis, Ammannito, et al., 2020). Similar to hydrated NaCl (e.g., Thomas et al., 2017; Vu et al., 2016), reflectance spectra of MHC and AMC (Coleyshaw et al., 2003; Tanaka et al., 2019) could be useful in the interpretation of observations of fresh surface materials. Given that the metastable carbonates transform into thermodynamically stable carbonates of calcite, magnesite, and dolomite in a certain amount of time after entrapment within ice, the presence of these metastable phases could be used to estimate the timing of eruption.…”
Section: Implications For Subsurface Brine Reservoirs On Icy Bodiesmentioning
confidence: 99%